DUOLINGO GAMIFICATION IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Sitti Nurjannah; Muthmainnah Mursidin; Mega Seltia (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
This research aims to determine how is the implementation of the Duolingo application in Improving Students’ Vocabulary Mastery of Eighth Grade at SMPN 23 Simbang Maros. The research design is Classroom Action Research (CAR) because the problem originates from the teaching and learning process in the classroom. The instruments were observation sheet, and test. The researcher conducted research on how far students understood vocabulary and how much students were able to understand and have a lot of vocabulary. The learning media Duolingo application is used to determine students understanding. The results of this research indicate that the improvement of students’ vocabulary mastery was attained it was denoted by the students’ test scores. The result of the data showed that the action and the implementation of the Duolingo application improved, indicated that Duolingo is effective to teach vocabulary. Furthermore, the application can be played individually or in groups which will create an enjoyable learning atmosphere.